(untitled) (INNOVATIVE ECONOMY, 2023)
Zapukhliak V.Z., Zastavnyi A.R. SECURITY CHALLENGES TO SOCIAL AND ECONOMIC PROGRESS IN THE MIDDLE EAST Purpose. The aim of the article is to assess the main security challenges in the Middle East, determine their impact on economic development and social progress in the region, and outline priorities for ensuring the social and economic development of countries in current conditions. Methodology of research. The methodological basis of the study is based on a dialectical approach. A combination of general scientific and special research methods was used to achieve the set goal, ensuring the reliability of the results: historical-logical method – to substantiate the historical nature of security challenges in the Middle East, system analysis method, methods of induction and deduction – for formulating hypotheses and conclusions about the impact of security challenges on social progress in the region, comparative method – to identify differences in the economic development of Middle Eastern countries, graphical visualization method. Findings. It is substantiated that the Middle East is a region of geopolitical significance but is also characterized by a complex interaction of external influences and security challenges. The main external influences in the Middle East are systematized and classified. The main security challenges in the Middle East are identified and detailed. The main factors of tension in the countries of the Middle East are revealed. The role of external actors in deepening tensions in the region is confirmed, and attention is focused on the growth of regional competition. The geopolitical landscape of the Middle East is characterized by regional rivalry for power, especially between Iran and Saudi Arabia. It is argued that problems in the social and economic sphere are an additional source of instability in the region. The level of unemployment in Middle Eastern countries is analysed, and attention is focused on the need to reduce the proportion of unemployed youth. Significant differences between countries in the region in terms of GDP per capita are confirmed. An assessment of the impact of security challenges in the region on the social progress of countries and the identification of the main dependencies are conducted. Originality. The main factors of tension in the Middle East region are identified, and the main external influences on the Middle East, which can have historical, political, economic, cultural, and religious character, are detailed. Further development is given to identifying the consequences of the intervention of external actors in the domestic policy of countries, leading to the aggravation of the security situation in the region. The impact of security challenges on the economic development of countries, which has significant inequality, is argued and the level of impact on ensuring social progress is assessed. Practical value. The substantiated results of the study and the obtained conclusions can be used in determining the strategic vectors of the social and economic development of countries in the context of security challenges and external influences. Key words: security challenges, geopolitical competition, regional actors, external influences, Middle East, economic development, unemployment, GDP per capita, social progress, Global Terrorism Index, Democracy Index, Peace Index, Corruption Perceptions Index.